2007
DOI: 10.1080/01612840601096321
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy and Locus of Control Affect Management of Aggression by Mental Health Nurses

Abstract: The safe and effective management of aggression has become an increasingly critical skill for mental health nurses, particularly those working in acute inpatient settings. There is considerable evidence to suggest that the psychological constructs of self-efficacy and locus of control are closely related to work performance in a variety of occupations. By drawing upon literature published in the past 15 years, this paper highlights this evidence and draws attention to the relationship between self-efficacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
(97 reference statements)
0
20
0
1
Order By: Relevance
“…In psychiatry, Dunn et al. () argue for a direct relation between mental nurses' self‐efficacy and their ability to effectively manage aggression. Similarly, self‐efficacy is one of the factors which improve physicians' performance (Overeem et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In psychiatry, Dunn et al. () argue for a direct relation between mental nurses' self‐efficacy and their ability to effectively manage aggression. Similarly, self‐efficacy is one of the factors which improve physicians' performance (Overeem et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Lee and Ko (2010) and Manojlovich (2005) both report that improved self-efficacy may improve nursing performance. In psychiatry, Dunn et al (2007) argue for a direct relation between mental nurses' selfefficacy and their ability to effectively manage aggression. Similarly, self-efficacy is one of the factors which improve physicians' performance (Overeem et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and that D‐E&R teams ability to manage inpatient violence improves with increased self‐efficiency of its members (Dunn et al . ). It can be concluded that research has shown significant relations between these factors, but little is known about the attributes that characterize self‐efficient D‐E&R teams.…”
Section: Introductionmentioning
confidence: 97%
“…First, the confidence in the ability to work with aggressive patients is considered a valuable outcome (Martin & Daffern 2006). Second, with regard to Bandura's research related to the impact of self-efficacy belief on performance (Dunn et al 2007), the Confidence in Managing Patient Aggression Scale may be a predictor of performance results, and therefore DABS would be dispensable. However, we do not have enough evidence that Thackrey's instrument really predicts performance in managing patient aggression.…”
Section: Introductionmentioning
confidence: 99%